Perspektif Guru Dalam Penerapan Pembelajaran Outdoor Learning Terhadap Kreativitas Siswa Di Sekolah Dasar Negri Se-Kecamatan Cibeunying Kidul - Sagala, Josua; Sunarya, Dede Tatang; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2020)
At the elementary school level there is a science learning that discusses all about natural events, science learning requires the ability of student creativity so that learning can run well, to assist teachers in bringing out student creativity, teachers can implement outdoor learning learning. With outdoor learning, the teacher can involve students' creativity in learning science. This study aims to look at the teacher's perspective in the application of outdoor learning to student creativity in public elementary schools in the Cibeunying Kidul sub-district. The research method uses quantitative descriptive and the research design is survey. Data collection techniques in this study using a questionnaire with the form Google, population and samples in this study were teachers who were found in 10 elementary schools in the Cibeunying Kidul sub-district, the conclusion of this study there was an influence between outdoor learning and student creativity.